PENGARUH KOMITE AUDIT, INDEPENDENSI KOMITE AUDIT, DAN PROFITABILITAS TERHADAP AUDIT REPORT LAG DI PERUSAHAAN MANUFAKTUR - Cahya Gunarsa, I Gede Aditya; Dwija Putri, IGAM Asri (E-Jurnal Akuntansi, 2017)
This study aims to determine effect of the audit committee, audit committee independence, and profitability of audit report lag in Manufacturing Companies Listed On BEI 2013-2015. Sampling method is purposive sampling nonprobability sampling. Data analysis method is multiple linear regression analysis. Audit Report Lag can be defined interval time from the date closing of annual financial statements until date specified in the independent auditor's report or in some studies declared the audit delay. Audit Report Lag as phenomenon influenced by various factors are driving the emergence of phenomenon. Audit committee, audit committee independence, and profitability is believed can affect audit report lag. Based on research results obtained show audit committee, audit committee independence, and profitability negatively affect of audit report lag. This shows that more the number of audit committee and higher of audit committee independence and higher profitability, the company will not experience delays in submission of financial statements.
Keywords: Audit Committee, Audit Committee Independence, profitability, Audit Report Lag